2018
DOI: 10.2174/1874331501812010164
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Soil Thermal Diffusivity Using Pedotransfer Functions with Nonlinear Regression

Abstract: Background and Objective:Pedotransfer Functions (PTFs) are widely used for estimating soil thermal diffusivity. Some attempts have been made to indirectly predict soil thermal diffusivity from the easy available fundamental soil physics properties. The aim of the work was to validate usage PTFs with Nonlinear Regression (NLR) for estimating soil thermal diffusivity (KD), moreover was to select the best predictor variables used for determination of PTFs.Materials and Methods:Soil thermal diffusivity was measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Data were analyzed by using IBM statistical software SPSS version 16.0 (and Microsoft Excel 2016 (Arkkelin, 2014;Mady and Shein, 2018).One-way ANOVA was used for testing significant differences of different soil physiochemical properties in different land use system at 95% of confidence interval.…”
Section: Discussionmentioning
confidence: 99%
“…Data were analyzed by using IBM statistical software SPSS version 16.0 (and Microsoft Excel 2016 (Arkkelin, 2014;Mady and Shein, 2018).One-way ANOVA was used for testing significant differences of different soil physiochemical properties in different land use system at 95% of confidence interval.…”
Section: Discussionmentioning
confidence: 99%
“…Some models allowed to derive an inverse information on the soil bulk density by the measured data of the volumetric heat capacity or thermal conductivity and water content (Ochsner et al, 2001b;Lu et al, 2016). The soil thermal diffusivity at different water content was estimated from easily available data on soil texture, bulk density, and organic matter content (Mady and Shein, 2018). It was concluded that the best results for D were received when was taken into account the percentage of sand, silt, and clay (soil texture).…”
Section: Introductionmentioning
confidence: 99%
“…PSD measured by PM is widely used for estimation of soil hydro-physical properties such as saturated hydraulic conductivity (Shein et al, 2015;Mady and Shein, 2018a), soil water retention curve (Makó et al, 2014;Lamorski et al, 2014) and hysteresis of soil water retention curve (Lamorski et al, 2017;Shein and Mady, 2018;Mady and Shein, 2018b;Shein et al, 2019). Also, it has been used for calculation of soil thermal-physical properties such as thermal diffusivity (Mady and Shein, 2018c). There are many programs used PSD as an input data such as Rosetta, RETC, and HYDRUS-1D programs (Šimůnek et al, 2008).…”
Section: Introductionmentioning
confidence: 99%